1997
DOI: 10.1074/jbc.272.37.23247
|View full text |Cite
|
Sign up to set email alerts
|

Unliganded Epidermal Growth Factor Receptor Dimerization Induced by Direct Interaction of Quinazolines with the ATP Binding Site

Abstract: (11,12), suggesting a more than passive role of the IC domain in dimerization.The requirement for the EGFR tyrosine kinase activity in cellular signaling is based upon observations that receptors in which Lys-721 within the ATP binding site has been mutated and, hence, lack detectable kinase activity, do not display the full range of biochemical responses (13-15). This apparent requirement for kinase activity has focused attention on the development of drugs capable of blocking kinase activity specifically. Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
86
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(96 citation statements)
references
References 55 publications
8
86
2
Order By: Relevance
“…It is thus of major interest that several quinazoline-based chemicals have been demonstrated to compete with ATP binding to protein tyrosine kinases to inhibit various intracellular signalling pathways (Rewcastle et al, 1995). The mechanism of action for quinazoline-based TKI involves prevention of the transmembrane tyrosine kinase phosphorylation by competing with the ATP-binding site on the receptor (Arteaga et al, 1997). The presence of this component may provide additional valuable insights into the molecular mechanisms for a1-adrenoceptor antagonist-mediated apoptotic action in tumour cells (Anglin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It is thus of major interest that several quinazoline-based chemicals have been demonstrated to compete with ATP binding to protein tyrosine kinases to inhibit various intracellular signalling pathways (Rewcastle et al, 1995). The mechanism of action for quinazoline-based TKI involves prevention of the transmembrane tyrosine kinase phosphorylation by competing with the ATP-binding site on the receptor (Arteaga et al, 1997). The presence of this component may provide additional valuable insights into the molecular mechanisms for a1-adrenoceptor antagonist-mediated apoptotic action in tumour cells (Anglin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of anti-EGFR antibodies would improve the efficacy of TKIs, as it would keep the receptor inactive once the TKIs disassociate. This model provides a possible explanation for the efficacy of the combination of TKIs with anti-EGFR antibodies, especially in conditions when the ligands are present in limiting amounts (Arteaga et al, 1997;Lichtner et al, 2001;Gan et al, 2007). Besides the enhanced receptor stability, it is possible that the increased receptor number could also play a role in the observed enhanced co-immunoprecipitation of EGFR or HER3 with HER2.…”
Section: Effects Of Lapatinib and Trastuzumab On Bt474 Xenograftsmentioning
confidence: 97%
“…Inactive EGFR/ HER dimers also occur after therapy with EGFR TKIs (Anido et al, 2003). The binding of these agents to the ATP pocket of the receptor perturbs its three-dimensional structure, stabilizing interactions among receptors and promoting the accumulation of inactive EGFR dimers (Arteaga et al, 1997;Gan et al, 2007). The presence of high levels of EGFR inactive dimers on the cell surface would also act as a ligand trap, being able to bind (and sequester) the ligands without consequent receptor phosphorylation.…”
Section: Effects Of Lapatinib and Trastuzumab On Bt474 Xenograftsmentioning
confidence: 99%
“…These observations clearly suggest that the activity of ZD1839 on ErbB-2 phosphorylation is mediated by the EGFR. Interestingly, Arteaga et al (1997) have previously shown that quinazoline EGFR-TKIs induce the formation of EGFR/ErbB-2 heterodimers in SK-Br-3 cells even in the absence of ligands. Experimental data suggest that treatment with ZD1839 also affects ErbB-3 signaling.…”
Section: Mechanism Of Action Of Egfr-tkismentioning
confidence: 99%